2011
DOI: 10.3109/10253890.2011.562939
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in chronically defeated male mice: Behavioral, endocrine, immune, and neurotrophic changes as markers of vulnerability to the effects of stress

Abstract: This study aimed to analyze different behavioral profiles in response to chronic social defeat using the sensorial contact model. We hypothesized that a passive profile, unlike an active one, would be associated with behavioral and physiological characteristics related to depression. Six-week-old OF1 male mice were subjected to defeat for 21 consecutive days. A combination of cluster and discriminant analyses of the behavior exhibited during confrontation on Day 21 established two behavioral profiles: active (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 64 publications
1
34
0
3
Order By: Relevance
“…Previous studies in our laboratory using the chronic social defeat stress model revealed that subjects who adopt a passive behavioral profile, which is characterized by a higher immobility and lower social and nonsocial exploration than the active subjects, have an exaggerated corticosterone response following repeated defeat and low resting levels of corticosterone several days after the end of the chronic defeat experience [5,19]. Human studies report similar patterns in cortisol levels following prolonged periods of stress [20,21].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Previous studies in our laboratory using the chronic social defeat stress model revealed that subjects who adopt a passive behavioral profile, which is characterized by a higher immobility and lower social and nonsocial exploration than the active subjects, have an exaggerated corticosterone response following repeated defeat and low resting levels of corticosterone several days after the end of the chronic defeat experience [5,19]. Human studies report similar patterns in cortisol levels following prolonged periods of stress [20,21].…”
Section: Introductionmentioning
confidence: 54%
“…The behavioral evaluation was carried out using The Observer 3.0 (Noldus ITC, Wageningen, the Netherlands). To classify the subjects according to behavior, two cluster analyses were performed on all of the defeated mice based on the behavioral characteristics they displayed in the social confrontation on days 18 and 21 using the mean percentage of time spent on each assessed behavioral element [19]. …”
Section: Methodsmentioning
confidence: 99%
“…Aging in rodents resulted in diminished place preference conditioned to a food (Rubinow et al, 2009), nicotine, cocaine, morphine and alcohol (Vastola et al, 2002;Campbell and Wood, 2000). It is also associated with lower novelty exploration (Vastola et al, 2002;Campbell and Wood, 2000) and decreased scores of grooming (Scimonelli et al, 1999;Shoji and Mizoguchi, 2011), which are considered to reflect a reduced self-rewarding activity (Pothion et al, 2004;Dubreucq et al, 2010;Gómez-Lázaro et al, 2011;Park et al, 2011). Together, these findings from animal studies parallel clinical features of elderly depression, which are predominantly related to hedonic deficits (Gallo et al, 1994(Gallo et al, , 1997.…”
Section: Introductionmentioning
confidence: 77%
“…It has been shown many times that the Bdnf and Creb genes are involved in the brain mechanism of chronic social defeat stress [26,[34][35][36][37][38]. At the same time, the experimental evidence of the role of these genes in the mechanisms of aggression is scarce and inconclusive.…”
Section: Discussionmentioning
confidence: 99%